2018
DOI: 10.7883/yoken.jjid.2017.019
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Immune Responses to Outer Membrane Antigens OMP10, OMP19, and OMP28 of <i>Brucella abortus</i>

Abstract: SUMMARY:Brucella infection is accompanied by cytokine production, which serves as an important factor to evaluate the innate and adaptive immune responses. Several researchers have been investigating the mechanisms involved in Brucella infection in the host. Here, we conducted an analytical study to define pathogenic pathways and immune mechanisms involved in Brucella infection by investigating the antigenic efficacy of recombinant outer membrane protein 10 (rOMP10), outer membrane protein 19 (rOMP19), and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…More importantly, membrane proteins are the first contact in the interaction of bacteria and host cells (46). We found that compared with A19, the expression level of Omp25, Omp10, Omp19, Omp28, Omp2a and BCSP31 of A19BG were significantly no reduction, retains comparable cell membrane composition to A19 (47). Because these proteins have good immunogenicity, A19BG can induce a strong immune response after booster immunization (Table 1).…”
Section: Discussionmentioning
confidence: 86%
“…More importantly, membrane proteins are the first contact in the interaction of bacteria and host cells (46). We found that compared with A19, the expression level of Omp25, Omp10, Omp19, Omp28, Omp2a and BCSP31 of A19BG were significantly no reduction, retains comparable cell membrane composition to A19 (47). Because these proteins have good immunogenicity, A19BG can induce a strong immune response after booster immunization (Table 1).…”
Section: Discussionmentioning
confidence: 86%
“…In recent years, some studies have been focusing on new approaches searching for epitopes to diagnose infectious diseases such as immunoinformatic-based prediction or scanning of major antigen proteins [42]. In the case of brucellosis, increased interest has been shown in the use of the outer membrane proteins omp10, omp16, omp19, omp25, and omp31 to improve diagnosis performance by serological methods [43,44] but the detection of positive serum by protein alone is still limited [45]. The use of recombinant proteins such as BP26 has evidenced promising results with a diagnosis accuracy of 96.45% in humans and 95% in goats but has shown cross-reactivity with Vibrio parahaemolyticus, Listeria monocytogenes, Legionella pneumophila, Salmonella, and Vibrio parahaemolyticus [45].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of recombinant plasmids and purified recombinant proteins was performed as described previously (Im et al ., 2018; Huy et al ., 2020a,b). In brief, the open reading frames (ORFs) of the four B. abortus genes, namely, L7/L12 (BAB1_1265, 375bp), omp22 (BAB1_1302, 639bp), omp25 (BAB1_0722, 642bp) and omp31 (BAB1_1639, 786bp), were amplified by PCR from the S2308 genome using their respective primer pairs (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…More studies have been reported on the protective efficiency of recombinant Brucella proteins as subunit vaccine against Brucella infection. These single SSVs include outer membrane protein (OMP) 10 (Im et al ., 2018; Shim et al ., 2020), OMP19 (Im et al ., 2018; Shim et al ., 2020), OMP28 (Im et al ., 2018), BP26 (Gupta et al ., 2019), 50S ribosomal protein L7/L12 (Gupta et al ., 2019), VIRB10 (Pathak et al ., 2018), BCSP31 (Xu et al ., 2019) and P39 (Tadepalli et al ., 2017). Based on previous results, combined subunit vaccine (CSV) using more than two recombinant proteins could confer higher potential immune response against Brucella infection than SSV.…”
Section: Introductionmentioning
confidence: 99%